(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The use of xenotransplantions, potentially useful in solving one of the most serious problems of clinical transplantology, ie the lack of organ donations, still raises a multitude of doubts. They concern not only the practicability of this technique, but above all the lawfulness of the use of animals for the improvement of the living conditions and well-being of the human being. Moreover, the legal problems of this new kind of transplantation are not less important. In particular, in this perspective, and in order to give an initial answer to the issues concerning the admissibility of xenotransplantations, the analysis focuses on the contents of Legislative Decree 4 March 2014 n. 26, that gives implementation to Directive 2010/63 on the protection of animals used for scientific purposes. It is in the transposition of the European act, in fact, that the Italian law-maker establishes the clear prohibition of any experimentation aimed, through the use of animals, to research on xenografts. This prohibition, however raises a number of critical observations. Indeed, it seems to be contrary to the interests of research, not very careful with regard to the prospects of treatment for the benefit of patients, consequent to the possible development of scientific knowledge on the subject, and also contradictory with respect to the purposes, although unavoidably pursued, of safeguarding the well-being of non-human living subjects subjected to experimental procedures.